Perancangan dan Pembuatan Website Computer Science Student Association Universitas Prisma - Samuel Towoliu; Feibe Lawalata (Program Studi Teknik Informatika, 2026)
The rapid development experienced by mankind, especially in the field of technology today, has brought us to an era where everything is digitized. So it is not surprising that everything must be in the digital field or on the internet. This has changed from previously being a matter of choice for the community, whether you want to make it or not, but now it has become an obligation. This is necessary so that we can be well known and accepted in the wider community. Himpunan Mahasiswa Ilmu Komputer Universitas Prisma or known as the U-Prisma Computer Science Student Association (CSSA Prisma) in carrying out its functions and duties provides excellent and informative service to all members. Driven by this obligation, an information portal is needed as a place to publish information about CSSA Prisma. The information portal is in the form of a website. The website of CSSA Prisma was created to provide a forum for administrators to share official information, as well as for writers to work on producing good articles. These things are realized by the presence of various features on this website, such as profiles from the Student Association itself, activity galleries, and news portals, which cover various topics grouped into several categories. Making this website using HTML, PHP, CSS and JS as programming languages. And for database support, use the MySQL module. In the process also used Bootstrap.